Analysis of Students' Understanding of Temperature Concepts Based on Diagnostic Test Results: A Discovery Learning Study - David Tuhurima; John Rafafy Batlolona (Pascasarjana, Mataram University, 2026)
This study highlights the low conceptual understanding of students in physics learning, which is often accompanied by misconceptions, especially in the topic of temperature and heat. The purpose of this study is to analyze the improvement of students' conceptual understanding through the application of the Discovery Learning (DL) model. The study used a qualitative descriptive design supported by quantitative data in the form of a pretest and posttest. The subjects were 30 students of class VII-A who were selected purposively. The instrument used was an essay test to measure students' conceptual understanding before and after learning. The results showed a significant increase in students' conceptual understanding, indicated by an increase in scores from the low category in the pretest to the high category in the posttest. The DL model has been proven to be able to increase student activeness, encourage critical thinking processes, and help students build concepts independently through systematic learning stages. In addition, student misconceptions were still found regarding the concepts of temperature and heat that stem from inaccurate initial understanding. The conclusion of this study shows that the application of the Discovery Learning model is effective in improving students' conceptual understanding and reducing misconceptions, making it suitable for use as an alternative for more meaningful learning in physics